Impact of Androgen Deprivation Therapy on Overall Mortality in Prostate Brachytherapy Patients With Low Pretreatment Testosterone Levels. (July 2018) - Taira, Al V.; Merrick, Gregory S.; Galbreath, Robert W.; Butler, Wayne M.; Adamovich, Edward
Abstract : Objectives: To evaluate whether the use of androgen deprivation therapy (ADT) in prostate brachytherapy patients impacts overall mortality (OM) in patients with lower pretreatment serum testosterone levels compared with those with normal or high baseline serum testosterone. Materials and Methods: From October 2001 to May 2014, 1916 patients underwent brachytherapy and had a pretreatment serum testosterone. Baseline serum testosterone values were collected prospectively before initiation of therapy. Median follow-up was 7.2 years. In total, 26% of the patients received ADT, primarily men with higher risk disease. OM and prostate cancer–specific mortality were examined to determine whether men with lower baseline serum testosterone were at increased risk of mortality when ADT was used, compared with men with baseline normal or higher testosterone. Results: Prostate cancer–specific mortality and OM at 10 years was 0.8% and 22.0%. Age, tobacco use, diabetes, cardiovascular disease, and percent positive biopsies were the strongest predictors of OM. ADT use by itself was not associated with an increased risk of OM on multivariate analysis ( P =0.695). However, ADT use in men with lower baseline testosterone was associated with a significantly higher risk of OM ( P <0.01). ADT use in men with normal or higher baseline testosterone was not associated with an increased OM risk ( P =0.924). Conclusions: Men with lower baseline testosterone may be at increased risk of premature death when ADT is utilized compared with men with baseline normal or higher testosterone. Further analysis of this potential risk factor is warranted to further identify subsets of men who may be at higher risk of long-term adverse sequelae from ADT.